Experimental Study of Using Bentonite Concrete with and Without Crimbed Steel Fiber in Conventional Concrete. - Kalaiselvan, R; Madhan kumar, J; Raghul raj, B (International Journal of Engineering and Technology, 2018)
Cement manufacturingÂ Â pollutes atmosphere by release of greenhouse gases like carbondioxide and it depletes the ozone layer causing adverse affect on livings on earth by global warming. Due to this reason mineralÂ admixtures are added to concrete to reduce carbondioxideÂ emmision inÂ concrete.various type of mineral admixtures are available fly ash, silica fume, rice husk, sea shell and a cheaperÂ clay materialÂ bentonite is considered and used in this project.This paper presents the result of an experimental investigation carried out to evaluate the properties of concrete with bentonite and steel fiber bentonite in which ordinary portland cement was partially replaced with bentonite by weight for a mix of M25 grade concrete. Replacing of cement by bentonite and bentonite with steel fiber was carrird out, concrete was casted and tested for the compressive strength, split tensile strength and flexural strength. Mix of bentonite with conventional concrete for various percentage and the results have been tabulated and compared with conventional concrete. Then, the same properties were examined in concrete adding different percentages of crimed steel fiber by weight of concrete with constant amount of bentonite which in turn increases the strength of concreteÂ